Methodology of cash flows analysis - Pavlović Miloš (Viša ekonomska škola Peć, Leposavić, 2021)
Cash flows are one of the main indicators of liquidity and solvency of the company. In practice, the Statement of cash flows is very often done as "following document" to Balance sheet and Income statement. This is wrong. The statement of cash flows can give the information to its users about the ability of the company to make cash. The balance sheet and Income statement, due to their accrual basis, are not saying anything about the cash flows of the accounting period, and that is why the Statement of cash flows is very important. A good analysis of this statement can be the basis and support to the process of decision making both for internal and external users of financial information. In this paper we are presenting the methodology of the Statement of cash flows report analysis. The subject of this paper is the analysis of the Cash Flow Statement. The aim of this paper is to point out the importance of reporting on cash flows and its information capabilities to users of accounting information.